What is the best method for debonding metallic brackets from the patient’s perspective? - Pithon, Matheus Melo (Prog Orthod, 2015)
BACKGROUND: The aim of this clinical investigation was to compare the level of discomfort reported by patients during the removal of orthodontic metallic brackets performed with four different debonding instruments. METHODS: The sample examined in this split-mouth study comprised a total of 70 patients (840 teeth). Four different methods of bracket removal were used: lift-off debonding instrument (LODI), straight cutter plier (SC), how plier (HP), and bracket removal plier (BRP). Prior to debonding with all experimental methods, the archwire was removed. Before appliance removal, each patient was instructed about the study objectives. It was explained that at the end of debonding in each quadrant, it would be necessary to assess the discomfort of the procedure using a visual analog scale (VAS). This scale was composed of a millimeter ruler scoring from 0 to 10, in which 0 = a lot of pain, 5 = moderate pain, and 10 = painless. The level of significance was predetermined at 5 % (p = 0.05), and the data were analyzed using the BioEstat 5.0 software (BioEstat, Belém, Brazil). RESULTS: The pain scores with SC were significantly higher than in all other methods. There were no significant differences between HP and BRP pain scores, and the LODI group showed the lowest pain scores. Statistically, significant differences were observed in the ARI between the four debonding methods. LIMITATIONS: The biggest limitation of this study is that each tooth was not assessed individually. CONCLUSIONS: Patients reported lower levels of pain and discomfort when metallic brackets were removed with the LODI. The use of a straight cutter plier caused the highest pain and discomfort scores during debonding.